Asuhan Kebidanan Komprehensif pada NY “S” Di Bidan Praktek Swasta Bunda Kota Bukittinggi Tahun 2024 - Septri Wahyuni; Yuliza Anggraini; Mega Ade Nugrahmi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Comprehensive Care is continuous care from pregnancy to Family Planning (FP). Comprehensive care aims to provide quality services and prevent maternal and child mortality. The purpose of this case study is to provide comprehensive care to mothers from pregnancy, childbirth, postpartum, and newborn care using the documentation of the Seven Steps of Varney and SOAP. This assessment was conducted from January to April 2024 through data collection methods, interviews, and observations. Pregnancy care included three visits with the first day of the last menstrual period on July 12, 2023, and the expected delivery date on April 19, 2024. During the first, second, and third visits, the general condition of the mother was found to be good. Labor care was provided on April 24, 2024, at 11:30 AM when the mother came to the Midwife's Independent Practice, accompanied by her husband, complaining of abdominal pain since 08:00 AM and discharge mixed with blood. An internal examination revealed 4 cm dilation. At 4:00 PM, labor management was carried out. The delivery process was normal with the 60 Steps of Active Management of the Third Stage of Labor (AMTSL), the baby was born normal, male, weighing 2500 grams, with a length of 47 cm, and immediate newborn care was performed. Postpartum and newborn care proceeded smoothly without complications for both mother and baby.